Body mass index—predictor of outcome after coronary artery bypass grafting. (April 2013) - Shahabuddin, Syed; Perveen, Shazia; Furnaz, Shumaila; Fatimi, Saulat; Sami, Shahid; Sharif, Hasanat
Objective: Increased body mass index has been associated with increased postoperative morbidity. We studied the effect of body mass index in our population, using a modified scale suggested by the World Health Organization. Methods: From January 2006 to December 2008, 1019 patients undergoing first-time isolated elective coronary artery bypass grafting were selected from our cardiac surgery database. Data were analyzed by univariate and multivariate analyses. Results: Of the 1019 elective coronary artery bypass patients, 168 (15.8%) had a normal body mass index (18.5–22.9 kg·m −2 ) and 894 (84.2%) had a high body mass index (≥23.0 kg·m −2 ). There were 921 (86.7%) patients with 3-vessel disease, and 1012 (95.3%) had internal mammary artery grafts. The 30-day mortality was 0.8%. Multivariate analysis revealed age, hospital stay, perfusion time, and renal failure were significantly associated with hospital complications. High body mass index was not significantly associated with morbidity or mortality. The model had an adequate fit at p = 0.708 by the Hosmer and Lemeshow test. Conclusion: Increased body mass index alone is not a predictor of increased mortality and morbidity. In fact, these outcomes were associated with advanced age, hospital stay, perfusion time, and renal failure.